Güncel Kardiyoloji Pratiği - Karakayalı, Muammer; Omar, Timor; Kapucu, Murat Can; Küçüksu, Zafer; Kayan, Fethullah; Tüner, Haşim; Yetmiş, Furkan; Alıç, Enes; Coşkun, Ferhat; Koç, Şahbender; Tepe, Ömer; Böyük, Ferit; et al. (2023)
-